Anomalous correlation between quantum efficiency and transverse momentum spread in semiconductor cathode photoemission - Peng-Wei Huang; Houjun Qian; Ye Chen; Matthias Gross; Igor Isaev; Christian Koschitzki; Mikhail Krasilnikov; Shankar Lal; Sven Lederer; Xiangkun Li; Osip Lishilin; David Melkumyan; et al. (Physical Review Accelerators and Beams, 2022)
The next generation of accelerator based scientific facilities, such as the megahertz repetition rate free electron laser and electron-ion collider, relies on photoelectron sources of high peak and high average brightness. Therefore, photocathodes with both low transverse momentum spread (TMS) and high quantum efficiency (QE) are required. The conventional positive correlation between QE and TMS leads to a tradeoff between peak and average brightness. In this study, a negative correlation between QE and TMS is experimentally observed for the first time on a semiconductor photocathode (Cs_{2}Te). Two models are proposed to explain such an anomalous correlation. One model considers the junction between the semiconductor cathode and the metal substrate in the case of slightly excessive cesium deposition, and the other model considers different Cs-Te composites. Our studies inspire a new way to break the conventional correlation between QE and TMS, and open a new perspective to advance the beam brightness frontiers.